Rethinking Temporary Use Coordinators for the Regeneration of Underused Urban Spaces in Seoul - Kon Kim (The Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
This paper looks into a new policy framework of the Seoul Metropolitan Government that aims to create a new urban governance and use a citizens' participation as an urban regeneration tool. Particular attention is paid to the transformation process of new urban governance and its contribution to the regeneration process of underused urban spaces in the long term. Using a case study approach, a link was identified between the roles of coordinator groups and the long-term legacy of reuse of underused urban spaces. This trend is contextualised within the hierarchical fiscal mechanism in which new urban programmes are established and implemented. The findings emphasise the constant role of coordinator groups and the significance of the soft content curated by them in the regeneration process of the underused urban spaces in Seoul. Abstrak. Makalah ini melihat kerangka kebijakan baru dari Pemerintah Metropolitan Seoul yang bertujuan untuk menciptakan tata kota baru dan menggunakan partisipasi warga sebagai alat regenerasi perkotaan. Perhatian khusus diberikan kepada proses transformasi pemerintahan kota baru dan kontribusinya terhadap proses regenerasi ruang perkotaan yang kurang dimanfaatkan dalam jangka panjang. Dengan menggunakan pendekatan studi kasus, hubungan telah diidentifikasi antara peran kelompok koordinator dan warisan jangka panjang dari penggunaan kembali ruang perkotaan yang kurang dimanfaatkan. Tren ini dikontekstualisasikan dalam mekanisme fiskal hirarkis di mana program-program urban baru ditetapkan dan diimplementasikan. Temuan ini menekankan peran menerus dari kelompok koordinator dan pentingnya konten lunak yang dikuratori oleh mereka dalam proses regenerasi ruang perkotaan yang kurang dimanfaatkan di Seoul.Kata Kunci. Penggunaan lahan sementara, taktik sehari-hari, koordinator strategis, pemerintahan kota.